Optimization of the Hybrid System for Micro Hydro, Photovoltaic and Biomass Power Generation in Senamat Ulu Village Using Homer Simulation - Syawal, Elsi Alfionita; Nazir, Refdinal (Jurusan Teknik Elektro Universitas Andalas, 2021)
Currently, the supply of electrical energy is still not fulfilled in some areas due to the depletion of conventional energy sources and fossil energy. The ideal alternative energy is renewable energy that does not have the potential to run out such as solar energy, biomass and water. Senamat Ulu is a village in Bungo Regency that has the potential for biomass power generation because it has a lot of palm oil plantations covering an area of 3,917 hectares with an average production of 6,901 tons per year. Based on the coordinates of the center of the village, simulation Homer scored solar radiation of 4.43 kWh / m2/ day for Ulu Senamat area. The purpose of this research is to obtain the amount of biomass energy potential and the optimal model for the hybrid system of power generation in Senamat Ulu Village. From the results of the study, it was found that the potential for electrical power from the biomass power plant in Senamat Ulu was 6,113.65 kW consisting of 2,189.08 kW shells and 3,924.57 kW palm fiber. The most optimal generator model is simulation I in terms of the smallest NPC and COE economies, namely NPC 275,091 and COE 0.0768/kWh where Biomass is 49,946 kWh/year at a cost of 0.0271/kWh, PV 26,681 kWh/year with electricity price of 0.107/kWh, Micro hydro 156.025 kWh/year with electricity price of 0.00992/kWh, Storage Li-ion 8,643 kWh/year and converter 288,331 kWh/year and the time required to payback is 5.8 years.Keywords:Â Optimization, NPC, COEÂ